Collective forestry regimes to enhance transition to climate smart forestry. (24th July 2022) - Brnkalakova, Stanislava; Melnykovych, Mariana; Nijnik, Maria; Barlagne, Carla; Pavelka, Marian; Udovc, Andrej; Marek, Michal; Kovac, Urban; Kluvánková, Tatiana
Abstract: As European mountain forests are a significant world carbon stock and sequester, they have a prominent position in climate policies and climate smart forestry (CSF) implementation. However, forest ecosystem services (ES) that are public or common goods (i.e., of carbon sequestration) face a traditional social dilemma of individual versus collective interests, which often generate conflicts, and result in the overuse of ES and resource depletion. In this article, we elaborate a conceptual analytical framework and use it in case studies selected in European mountain areas to analyse the potential of socio‐ecological systems to develop CSF. Collective self‐organized forestry regimes, as a form of social innovation, are the main focus, compared with centrally governed state regimes and forest management practices in municipal forests. A conceptual framework to analyse collective self‐organized regimes and compare these with other CSF‐applicable forestry regimes is elaborated using a mixed‐method approach, centered around the estimation of carbon sequestration potential. The results indicate that collective self‐organized forestry regimes can play a role in fostering the transition of European forestry towards CSF.